2004
DOI: 10.1097/00004703-200402000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Associations Among Familism, Language Preference, and Education in Mexican-American Mothers and Their Children

Abstract: ABSTRACT. Latino families who express a higher degree of familism are characterized by positive interpersonal familial relationships, high family unity, social support, interdependence in the completion of daily activities, and close proximity with extended family members. Retention of cultural values, such as familism, may be linked to positive health outcomes; however, little is known about how families retain culture of origin values in the face of acculturation pressures. The current study explores accultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 27 publications
0
44
1
Order By: Relevance
“…There appears to be something protective for broad mental health about maintaining Spanish language capacity, possibly indicative of wider social connections. A small study found that children who preferred to speak both English and Spanish had higher rates of familism than those who spoke Spanish only (Romero, Robinson, Haydel, Mendoza, & Killen, 2004). The positive mental health effect for those who think in English but maintain strong Spanish speaking capabilities requires further research.…”
Section: Self-rated Mental Healthmentioning
confidence: 98%
“…There appears to be something protective for broad mental health about maintaining Spanish language capacity, possibly indicative of wider social connections. A small study found that children who preferred to speak both English and Spanish had higher rates of familism than those who spoke Spanish only (Romero, Robinson, Haydel, Mendoza, & Killen, 2004). The positive mental health effect for those who think in English but maintain strong Spanish speaking capabilities requires further research.…”
Section: Self-rated Mental Healthmentioning
confidence: 98%
“…However, only one of these studies examined the impact of these parenting practices on child behaviors via child familism values such that maternal attitudinal familism was directly and indirectly associated with child prosocial behavior partially through child familism values ( Calderón-Tena et al, 2011). One other article at this stage examined family contextual predictors finding that higher levels of parental education were associated with higher maternal familism, and also surprisingly, preference for English or bilingualism was also associated with higher child familism ( Romero, Robinson, Haydel, Mendoza, & Killen, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Familism was measured with the Family Impact Scale; this scale was developed for diverse adolescents (Colon, 1998) and has demonstrated good reliability (α = .81) with a similar samples of Mexican heritage youth (Romero et al, 2004). There are two subscales for this measure (1) Family proximity -amount of time spent with family members; and (2) Parent Closeness -perception of closeness to parents.…”
Section: Familismmentioning
confidence: 99%